Milker’s nodule: An under‐reported and under‐diagnosed occupational infection - Poudel, Guru Prasad (Clin Case Rep, 2020)
Single or multiple minimal painful nodulo‐ulcerative lesions over hand in dairy farm worker suggest likelihood of Milker's nodule.Use of personal protective equipment and antiseptics suffice treatment without unnecessary investigation and medicine.